STUDY OF WAVE RUN-UP ON U-SHAPED BAYS - SULVIANURI, RANI
The study of wave run-up is needed in disaster mitigation due to tsunami or other ocean waves. Wave run-up is related to the horizontal inundation that can be reached by waves on land. The run-up height and inundation depend on the wave profile and topography profiles. In this thesis, a study is conducted regarding the wave run-up in a narrow bays. The mathematical model used to analyze the wave run-up is the Saint-Venant equations. The wave run-up in the bay is a two-dimensional problem, but for a relatively narrow and long bay the Saint-Venant equations can be reduced to a one-dimensional equations. The study of the wave run-up includes numerical and analytical studies. For the numerical study, the validation of the momentum conserving staggered grid (MCS) scheme is applied to the one-dimensional Saint-Venant equations. Simulation tests were carried out to solve the problem of initial and boundary conditions for several bay shapes and wave profiles. In the analytical study, the one-dimensional Saint-Venant equations is solved by using the hodograph transformation (Carrier-Greenspan transformation), so that analytical formulas can be obtained regarding the wave run-up, namely the height of run-up, inundation distance and wave velocity at the shoreline. The formulas obtained are used to validate the results of the numerical simulation test with the MCS scheme. The comparison of the simulation test results of the Saint-Venant equations with the MCS scheme match well with the analytical formulas. Thus, it can be concluded that the MCS scheme can be used to accurately simulate the wave run-up in a narrow bay.